PENATALAKSANAAN FISIOTERAPI PADA KONDISI TRIGGER FINGER DENGAN INTERVENSI ULTRASOUND (US), INFRARED (IRR) DAN TRANSVER FRICTION DI RSUD BENDAN KOTA PEKALONGAN - Swasta Raya Mantep Sasmito; Ade Irme Nahdliyyah (Pena Jurnal Ilmu Pengetahuan Dan Teknologi, 2013)
Trigger finger  described as a condition in which the locking finger joints in motion at the time of the position fleksi to position ekstensi. This is because the inflamation local or a swelling of the tendon  wrapping  fleksor  which  resulted  in  wrapping  it  can  not  be  normal  to  slide.  Pathology changes in the triger finger commonly occurs as tendon inflammation flekxor digitorum profundus (stenosis), due to thickening of the tendon sheath stenosing tenosynovitis, this causes a decrease of capacity  as  a  function  of  finger  motion  constraints,  the  presence  of  pain and muscle  spasm  and decreased  functional  ability  is  :  writing  disorders,  lifting  heavy  objects.  To  provide  efficient handling  and  effectiveness,  then  carried  out  an  inspection  method  that  measures  the  range  of motion (LGS) with tools goneometer, muscle strength with Manual Muscle Testing (MMT), pain measurement with Verbal Descriptive Scale (VAS), functional disability with Durous Hand Index (DHI). After  the  action  of  physiotherapy  during  6  time  there is  an  increase  in  range  of  motion (LGS),  decrease  in  pain  with  Verbal  Descriptive  Scale  (VAS),    increase  in  functional  disability with Durous Hand Index (DHI). Keywords : Trigger finger, LGS, MMT, VAS, Durous Hand Index.